The Meaning Behind the Scar: Anonymous Live Liver Donors' Perceptions of Their Surgical Scars. Issue 5 (25th May 2020) - Krause, Sandra; Pritlove, Cheryl; Abbey, Susan; Jung, Judy
Abstract : Background: Scarring can greatly impact quality of life for individuals (ie, causing depression posttraumatic stress disorder and body image issues). Those who wish to be anonymous live liver donors are warned of the potential negative psychological impacts associated with the large scar left from liver donation surgery. Given the unique degree of autonomy that these patients have over their surgery, we explore whether a sample of 26 anonymous live liver donors experience a unique relationship with their scar. Methods: Anonymous donors participated in a semistructured qualitative interview examining their experience with donation. Interviews were audio-recorded, transcribed, and analyzed using the constant comparison method for themes pertaining, to participants' perception of their scar. Results: Five main themes were identified—a marker of satisfaction about the donation experience, a physical reminder of donation, a trigger for recipient-related thoughts, an awareness tool, and a potential threat to anonymity. Donors did not voice any body image or cosmetic concerns due to their scars. Instead, discussions about the negative aspects of scarring centered around the identifying nature of their scar. Conclusions: These findings help underscore the distinctiveness of anonymous living liver donors as a patient population. Preparing anonymous living liver donors for different types of cosmetic issues relating to their scar (ie, as a possible threat to their desired anonymity) may be more appropriate than preparing them in the same way as other donor populations. Abstract :